Pengembangan Usaha Kedai Andi Di Indarung Kota Padang Provinsi Sumatera Barat - Abdilla, Mohammad; Rosa, Yenni Del; Yendra, Nofri; Riski, Tri Rachmat; Rahmasari, Nisya Cesaryani (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
Andi shop business is located in Indarung, Padang city, West Sumatra province. So far, the business has not had any touch of Information Technology and Appropriate Technology. The food sold is priced at an average of IDR 8,000 per portion and various types of drinks are priced at IDR 5,000 per glass. In running its business, Andi shop is assisted by her wife and 3 children so that there is no payment of wages/salaries for workers. The turnover of Andi shop business is around IDR 600,000 per day. Marketing of Andi shop business is only around Indarung market and regular customers who routinely shop every day. Because there is always a continuous demand for food and drinks every day, the marketing prospects of Andi shop business are quite good to be developed in the future. The priority problem of Andi shop business is currently related to marketing problems with the solution of providing promotional counseling via digital marketing to expand market segmentation to consumers. The method of implementing activities is in accordance with the solutions offered in the form of discussion methods, counseling and practice. The purpose of community service activities is so that partners can develop well and continue in the future in the long term. Partner income is also expected to increase by around 10% per year so that it can increase the income of Andi shop business owners in particular and the economy of Padang city and West Sumatra province in general.